Sources of daily stress and its physical and psychological manifestation in primary school children - Jurin, Tanja (2011)
The purpose of this study was to determine the sources of stress in school children, as well as association between total stress intensity, physical and psychological manifestations. Further, gender and age differences were examined. The study was conducted on a sample of 179 male and 177 female pupils, aged between 10 and 14, from a single elementary school in Zagreb, Croatia. Sources of stress (estimated levels of stress in specific areas of pupils’ life), physical reactions to stress (a silhouette on which they indicated in which parts of the body they felt stress) and psychological measures (depression, trait anxiety, anxiety sensitivity, self esteem) were examined. The strongest source of stress for children of both genders was school. With increasing age, the areas of school, parents and physical appearance represented more intense sources of stress. The overall intensity of a child’s experienced stress was found to be associated with higher anxiety, anxiety sensitivity and depression, lower self esteem and greater number of marked body parts related to stress. The results of this study indicate that the quality and quantity of sources and manifestations of stress varies with gender and age throughout childhood. Furthermore, these results suggest the need for prevention of psychological and physiological effects of stress from an early age.
Projekt MZOS
ENG